Implementation of Rapid Whole Body Assessment (REBA) to Reduce Musculoskeletal Disorders (MSDs) to Improve the Post-Harvest Work System of Oil Palm - Sukapto, Paulus; Winata, Sally Feodora; Prakoso, Dito (Jurnal Improsci, 2025)
Background. Oil palm harvesting workers who work unergonomically often experience the risk of Musculoskeletal Disorders (MSDs) when using traditional harvesting tools, namely, egrek and angkong. Egrek is a tool for harvesting palm oil, and angkong is a tool for transporting oil palm from the plantation to a temporary shelter for palm oil. The unergonomic working position of palm oil workers during harvesting, combined with repetitive movements such as cutting leaves and picking palm oil, causes discomfort for the workers. Aims. Researchers designed ergonomic harvesting tools (egrek) and transport tools (angkong) to improve efficiency in oil palm harvesting. Researchers evaluated harvesting and transportation activities using the Nordic Body Map (NBM) questionnaire and the Rapid Whole-Body Assessment (REBA) method. Result. The analysis results showed that nearly all harvesting activities carry a high risk of MSDs. The respondents to this study were nine harvesters and 11 oil palm harvest workers who operated angkong. Conclusion. The results showed that harvesters often experienced discomfort in the buttocks and abnormal posture, and repetitive movements required to cut leaves and oil palm bunches. The results of the REBA calculation for palm harvest showed that it was very high (Very High), with scores of 12 when lifting the angle and 11 when pushing the corner. Therefore, immediate improvement was needed, as this had an impact on the risk of MSDs. Implementation. Also, the results of REBA's calculation for transporting oil palm bunches with angkong were 9. To reduce the REBA value by adding the angkong wheel so that the final REBA value is 7.